Stable benefits of bilateral over unilateral cochlear implantation after two years: A randomized controlled trial. (26th September 2016) - van Zon, Alice; Smulders, Yvette E.; Stegeman, Inge; Ramakers, Geerte G. J.; Kraaijenga, Veronique J. C.; Koenraads, Simone P. C.; Zanten, Gijsbert A. Van; Rinia, Albert B.; Stokroos, Robert J.; Free, Rolien H.; Frijns, Johan H. M.; Huinck, Wendy J.; et al.
Abstract : Objectives/Hypothesis: To investigate hearing capabilities and self‐reported benefits of simultaneous bilateral cochlear implantation (BiCI) compared with unilateral cochlear implantation (UCI) after a 2‐year follow‐up and to evaluate the learning effect of cochlear implantees over time. Study Design: Multicenter randomized controlled trial. Methods: Thirty‐eight postlingually deafened adults were included in this study and randomly allocated to either UCI or simultaneous BiCI. Our primary outcome was speech intelligibility in noise, with speech and noise coming from straight ahead (Utrecht–Sentence Test with Adaptive Randomized Roving levels). Secondary outcomes were speech intelligibility in noise with spatially separated sources, speech intelligibility in silence (Dutch phoneme test), localization capabilities and self‐reported benefits assessed with different quality of hearing and quality of life (QoL) questionnaires. This article describes the results after 2 years of follow‐up. Results: We found comparable results for the UCI and simultaneous BiCI group, when speech and noise were both presented from straight ahead. Patients in the BiCI group performed significantly better than patients in the UCI group, when speech and noise came from different directions ( P = .01). Furthermore, their localization capabilities were significantly better. These results were consistent with patients' self‐reported hearing capabilities, but not with the questionnaires regarding QoL. We found no significant differences on any of the subjective and objective reported outcomes between the 1‐year and 2‐year follow‐up. Conclusions: This study demonstrates important benefits of simultaneous BiCI compared with UCI that remain stable over time. Bilaterally implanted patients benefit significantly in difficult everyday listening situations such as when speech and noise come from different directions. Furthermore, bilaterally implanted patients are able to localize sounds, which is impossible for unilaterally implanted patients. Level of Evidence: 1b Laryngoscope, 127:1161–1168, 2017